Peranan Perempuan Terhadap Kesejahteraan Keluarga Kanjilo Kabupaten Gowa - Andi Dara Ulang,; ST. Aisyah BM, (Jurnal Berita Sosial, 2022)
The role of women in improving family welfare is very important in the welfare of family life. This type of research is descriptive qualitative research. Data was collected by conducting observations, interviews, documentation and reference searches. Data processing and data analysis techniques go through three stages, namely: data reduction, data presentation and conclusion drawing. The results showed that women's efforts to improve family welfare were women doing informal jobs such as cake sellers, fruit ice sellers, vegetable sellers, shop businesses, sewing craftsmen and fried food sellers. The role of women has a very large influence in increasing the fulfillment of the needs of life and is a very useful resource to improve family welfare. There are several obstacles faced by women in improving family welfare, namely education, business capital, lack of skills and marketing.